Soluciones no triviales para un problema de Dirichlet semilineal con múltiples valores propios no lineales (2011)
En este trabajo se demuestra que el problema elíptico semilineal tiene por lo menos tres soluciones no triviales. Una de estas es positiva, otra negativa y la tercera cambia de signo. La demostración se hace mediante el uso del Teorema de Paso de Montaña y el índice de Morse. / Abstract. In this paper prove that a semilinear elliptic boundary value problem has at least three nontrivial solutions when the range of the derivate of th nonlinearity includes at least the first two eigenvalues of the Laplacian and all solutions ar nondegenerate. A pair are of one sign (positive and negative, respectively). The one sign solution has Morse index greater than or equal to 2. Extensive use is made of the mountain pass theorem, and Morse index arguments of the type Lazer-Solimini (see [LS]).